Pengaruh Nilai Durabilitas Dengan Pemanfaatan Aspal Karet Alam Dan Zeolite Dengan Campuran Hangat Pada Lapisan Ac-Wc - Saleh, Alfian; Haris, Virgo Trisep; Saleh , Alfian (REKAYASA: Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2025)
<pre id="tw-target-text" class="tw-data-text tw-text-large tw-ta" dir="ltr" data-placeholder="Translation" data-ved="2ahUKEwil_cOC0pKKAxV-yTgGHY8HLYIQ3ewLegQIDBAU" aria-label="Translated text: The pavement layer is the outermost part of the road structure that directly receives traffic loads and functions as a solid surface for vehicles. Improving road quality can be done by improving the quality of the pavement layer used in flexible pavement work. One type is the AC-WC layer. So a study was conducted to increase the durability value by using natural rubber asphalt by adding zeolite as an additive to increase the durability value. The purpose of this study was to analyze the effect of the durability value of the natural rubber asphalt mixture with the addition of zeolite to the AC-WC road pavement layer as an additive in the mixing. Where the variation of zeolite content used starts from 0%, 0.5%, 1%, 1.5%, 2% and 2.5% with a soaking temperature of 60 ° C with a soaking time of 24 hours. The results obtained in this study the best durability value was obtained at 1% zeolite content of 91%, 1.5% zeolite content of 92%, 2% zeolite content of 94% and 2.5% zeolite content of 95%. So that it meets the 2018 Bina Marga Specifications Revision II of 2020. While at 0% and 0.5% zeolite content there was a decrease of 86% at 0% zeolite content and 87% at 0.5% zeolite content. The conclusion of the study on the effect of durability value on a mixture of natural rubber asphalt and zeolite with a warm mixture on the AC-WC layer is that the more zeolite content used in variations of 0% to 2.5% will affect the IKS value or residual strength index obtained will increase.">